Advances in Precision Agriculture: A Review of Technologies, Applications and Future Prospects - , Narinder Panotra; , Rajula Bheemannagari Deepika; , Pritam Roy; , Yashowardhan Singh; , Sandhya Sinha; , Narpat Choudhary; , Bhavesh Choudhary; , Anshu Gangwar; , Lalita Kumar Mohanty; , Ram Gopal (Archives of Current Research International, 2025)
Precision agriculture represents a transformative approach to modern farming that integrates advanced technologies to optimize crop production while minimizing environmental impact. This comprehensive review examines the current state of precision agriculture technologies, their practical applications, and future development prospects. Key technologies including Global Positioning Systems (GPS), Geographic Information Systems (GIS), remote sensing, Variable Rate Technology (VRT), Internet of Things (IoT), and artificial intelligence are analyzed for their contributions to agricultural efficiency. The review synthesizes findings from recent research demonstrating significant improvements in resource utilization, with water savings of 20-50% and fertilizer reduction of 15-30% while maintaining or increasing yields. Major applications span soil mapping, crop health monitoring, automated irrigation, and harvest optimization. Despite substantial benefits, challenges including high initial investment costs, technical complexity, and data management issues persist. Future prospects indicate continued growth driven by emerging technologies such as autonomous machinery, blockchain integration, and advanced machine learning algorithms. This review provides stakeholders with a comprehensive understanding of precision agriculture's current capabilities and future potential in addressing global food security challenges while promoting sustainable agricultural practices.